Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing 2010 - Lee, Roger.; Ma, Jixin.; Bacon, Liz.; Du, Wencai.; Petridis, Miltos. (Studies in Computational Intelligence, 2010)
The purpose of the 11th Conference Software Engineering, Artificial Intelligence, Networking, and Parallel/Distributed Computing (SNPD 2010) held on June 9 - 11, 2010 in London, United Kingdom was to bring together scientists, engineers, computer users, and students to share their experiences and exchange new ideas and research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them. The conference organizers selected 15 outstanding papers from SNPD 2010, all of which you will find in this volume of Springers Studies in Computational Intelligence.